Ground reaction force and electromyographic activity of transfemoral amputee gait: a case series http://dx.doi.org/10.5007/1980-0037.2013v15n1p16 - Alberto Carlos Amadio; Luis Mochizuki; Edward Yuji Yamaguti; Alex Sandra Oliveira de Cerqueira; Júlio Cerca Serrão (Universidade Federal de Santa Catarina, 2013)
Ground reaction forces (GRF) and electromyographic activity form a part of the descriptive data that characterise the biomechanics of gait. The research of these parameters is important in establishing gait training and understanding the impact of amputation and prosthetic components on movement during the act of walking. Therefore, this case series describes the GRF and electromyographic activity in the gait of transfemoral amputees. A force plate was used to measure GRF, and an electromyographic system monitored the vastus lateralis, biceps femoris, tibialis anterior, and gastrocnemius lateralis muscles of the non-amputated leg. The average vertical and anteroposterior GRF time-curves, average electromyographic activity, and descriptor variables were then analysed. We observed decreases in vertical and anteroposterior GRF magnitudes as well as in anteroposterior GRF descriptor variables during the propulsive phase in the amputated leg. There were increases in phasic muscle activity and co-activation in the non-amputated leg. We concluded that, during walking, the unilateral transfemoral amputees (who were analysed in this case series) developed lower GRF in the amputated limb and a longer period of electromyographic activity in the non-amputated limb.